Contrast between youtubers and traditional celebrities: impact in brand awareness, purchase intention and brand loyalty - Menezes, Inês Furtado (2018)
Social media platforms have been increasing in terms of usage and now, more than ever, consumers are using these type of websites as a way of receiving product information. Taking this into consideration, it has become strategic for brands to gain presence on these social sites as a way of connecting with their consumers and as a strategy to obtain new ones. Through the growth of these platforms, new opinion leaders started to emerge and celebrities are not just the ones we see in television or in movies. Social media stars, commonly known as digital influencers, are now being endorsed by multiple brands. These stars are believed to be more relatable and to have a bigger influential power over consumers. With YouTube being the second most used website in the world, these digital celebrities have been gaining voice. Hence brands are currently integrating YouTubers as endorsers in their marketing strategies. This dissertation studied the different impact in consumer behavior caused by endorsements featuring YouTubers in comparison to traditional celebrities. The research was made to portuguese individuals through an online survey. The findings suggest that YouTubers are seen as a more credible, trustworthy and attractive source of product information than traditional celebrities. Additionally, it was also attained that endorsements with YouTubers have a more positive influence over consumers’ brand awareness and purchase intention than endorsements with traditional celebrities. Overall, this research concluded that using YouTubers over traditional celebrities as brand endorsers is currently an efficient strategy that companies can implement.